COUNSELING ON REPRODUCTIVE DISORDERS MANAGEMENT IN FEMALE BEEF CATTLE LIVESTOCK GROUPS IN DALEGAN VILLAGE, PANCENG DISTRICT, GRESIK REGENCY - Suprayogi, Tri Wahyu; Susilowati, Suherni; Hermadi, Herry Agoes; Al Arif, M Anam; Hernawati, Tatik; Mulyati, Sri; Suwanti, Lucia Tri; Maslachah, Lilik; Kurnijasanti, Rochmah; Lestari, Tita Damayanti; Effendi, Mustofa Helmi; Hernanda, Ary Setya; Supriyadi; Saputra, Rakan Mahiid; Dewi, Aprilia Kurnia (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Management of reproductive disorders in female beef cattle (Bos taurus) is a vital step in enhancing livestock productivity and animal welfare. This educational activity was conducted in Dalegan Village, Panceng District, Gresik Regency, aiming to assist farmers in improving cattle reproductive performance through feed technology and supporting the development of modern farming practices. The methods applied included counseling, practical field demonstrations, and interactive discussions with participants, presented in a qualitative descriptive format. The results indicated an improvement in farmers' knowledge of the causes, clinical signs, and management steps for reproductive disorders such as anestrus, dystocia, and endometritis, as evaluated through pre-test and post-test assessments. Additionally, the activity provided guidance on the importance of feed management, cattle reproductive health, and modern farm management. In conclusion, this counseling successfully increased farmers' awareness of cattle reproductive health, which is expected to support the productivity of beef cattle farming in the region.